Practice-oriented solutions integrating intraoperative electron irradiation and personalized proton therapy for recurrent or unresectable cancers: Proof of concept and potential for dual FLASH effect - Calvo, Felipe A.; Ayestaran, Adriana; Serrano, Javier; Cambeiro, Mauricio; Palma, Jacobo; Meiriño, Rosa; Morcillo, Miguel A.; Lapuente, Fernando; Chiva, Luis; Aguilar, Borja; Azcona, Diego; Pedrero, Diego; et al. (Frontiers in Oncology, 2022)
Background: Oligo-recurrent disease has a consolidated evidence of long-term surviving patients thanks to the use of intense local cancer therapy. The latter combines real-time surgical exploration/resection with high energy electron beam single dose of irradiation. This results in a very precise radiation dose deposit, which is an essential element of contemporary multidisciplinary individualized oncology. Methods: Patients candidates to proton therapy were evaluated in Multidisciplinary Tumor Board to consider improved treatment options based upon the institutional resources and expertise. Proton therapy was delivered by means of a synchrotron- based pencil beam scanning technology. Results: In a period of 24 months 327 patients were treated with proton therapy: 218 were adults, 97 had recurrent cancer and 54 required re-irradiation. In 5 cases the integral strategy to optimize the local disease management was the combination of surgery, intraoperative electron boost components of the radiotherapy treatment and external pencil beam proton therapy. Conclusions: Individual case-solutions strategies combining intraoperative electron radiation therapy and proton therapy for oligo-recurrent or unresectable localized cancer patients are feasible. The potential of this combination can be clinically explored with electron and proton FLASH beams